ON NORMAL RULED SURFACES OF GENERAL HELICES IN THE SOL SPACE Sol3 - Ergut, Mahmut; Korpinar, Talat; Turhan, Essin (Inst Applied Mathematics, 2013)
In this paper, normal ruled surface of general helices in the Sol3 are studied. Also, explicit parametric equations of normal ruled surface of general helices in the Sol3 are found.
Keywords: general helix; Sol space; normal surface